Fish gut content from biological collections as a tool for long-term environmental impact studies - Manoel, Pedro Sartori [UNESP]; Azevedo-Santos, Valter M. [UNESP] (Springer Nature, 2018)
Most of the world’s fish fauna is suffering from different types of human impacts and new conservation tools are required. The fish diet analysis is a tool that has been used to evaluate degradation processes of aquatic environments, however, few long-term studies are performed by several reasons (e.g., lack of funding, opportunity). Our aim was to test whether the fish gut content from biological collections can be used for comparisons with current data and, consequently, be used as a tool for long-term environmental impact studies. We compared the gut content of fish preserved for fifteen years in a biological collection with recently sampled fish, considering the factors size of the specimen, preservation time and preservation form. We did not find differences in the gut content percentage of preservation between fish size classes and preservation time. However, we found differences between preservation form, in which the fish fixed in formalin kept the digestive content preserved while the fish preserved directly in alcohol did not. Thus, we encourage the use of fish gut content from biological collections fixed in formalin for long-term ecological studies. Our findings may help elucidate some long-term effects of human impacts on fish fauna.
Keywords: Diet; Fixation; Formalin; Icthyofauna; Stomach contents; Trophic ecology